Uncovering the roles of B lymphocytes in the NOD mouse model of type 1 diabetes through genetic engineering and therapeutic targeting - Wang, Qiming. (Tufts University. Tisch Library., 2019)
β-cell destruction in type 1 diabetes (T1D) is considered a T-cell mediated autoimmune manifestation, but based on studies in the NOD mouse model, B-lymphocytes also play a critical role in disease development. They do so by serving as a preferential subset of pathogenic antigen resenting cells (APC) that expand diabetogenic T cells. Immunological tolerance induction mechanisms that normally eliminate or inactivate autoreactive B-lymphocytes are defective in NOD mice and also in T1D patients. Our previous studies mapped a faulty NOD B-lymphocyte tolerance phenotype to a 6.22Mb region on Chromosome 4. With a combination of differential gene expression and ingenuity pathway analyses (IPA) we identified a hypomorphic Ephb2 allelic variant as a potential candidate gene that allowed the generation of pathogenic B-lymphocytes in NOD mice. We experimentally tested the candidacy of Ephb2 by creating a NOD mouse model transgenically expressing the Ephb2 allele from B6 origin (NOD-Ephb2B6). Expression of the B6 derived Ephb2 allele afforded significant T1D protection by attenuating the pathogenicity of B-lymphocytes. As a result of their involvement in the pathogenicity of T1D, B-lymphocyte-targeted therapies have received considerable interest as potential T1D interventions. However, in new-onset human T1D patients, rituximab (anti-CD20) mediated B-lymphocyte depletion was only partially effective as a possible disease intervention. Therefore, I tested whether other possible B-lymphocyte-directed approaches that either independently or in combination with anti-CD20 might provide an improved means for T1D inhibition. I found that both continuous and transient blockade of the fundamental B-lymphocyte survival factor BAFF protected NOD mice from T1D even when initiated at late disease stage characterized by the presence of insulin autoantibodies (IAA). B-lymphocytes surviving after BAFF blockade are functionally compromised in their ability to present autoantigens to T cells. Surprisingly, addition of anti-CD20 abrogated the protective effects of transient BAFF blockade. I found that this is due to B-lymphocytes that have immunoregulatory functions (Bregs) becoming enriched after transient BAFF blockade were sensitive to anti-CD20 mediated depletion. These Bregs are characterized by secretion of anti-inflammatory cytokine IL-10 and expression of the ecto-enzyme CD73 that converts inflammatory ATP to immunosuppressive adenosine. To dissect which one of these molecules was employed by Bregs to suppress autoreactive T cells, we created NOD-CD73null mice using CRISPR/Cas9 genome editing approach. NOD-CD73null mice developed T1D at similar rate as standard NOD controls. However, BAFF blockade mediated T1D protection is compromised in NOD.IL10null but not NOD-CD73null mice. Taken together, these data highlight a B-lymphocyte centric model in the etiology of T1D in which genetic approaches that restore faulty B-lymphocyte tolerance induction attenuates T1D development. Our cellular and molecular dissection of pathogenic versus regulatory B-lymphocyte subsets in NOD mice yields two important conclusions. First, the pattern of B-lymphocyte depletion elicited by rituximab treatment may underlie why the agent failed as a T1D intervention, whereas even when initiated at a late stage of disease development BAFF blockade that preferentially depletes pathogenic B-lymphocytes and enriches Bregs can provide an effective means to block progression to overt hyperglycemia. Second, IL-10 secretion instead of CD73 expression is a necessary component of BAFF blockade mediated T1D protection.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Genetics.; Advisors: David Serreze, and Henry Wortis.; Committee: Gareth Howell, Derry Roopenian, and Jennifer Trowbridge.; Keywords: Genetics, and Immunology.